Business Opportunity : Tedboy Bakery / Nur Amirah Makhtar - Makhtar, Nur Amirah (2021)
This assignment is for ENT300, this whole report is about business opportunity from chapter 4. In this report contain about how Ted Bakery create a new innovation product to sell to the customers. In this report I also introduced my company, background and our products. Ted Bakery prepared a new innovation product which is ”Healthy Berry Bread”. I will explain about the advantages of this new innovation in Tedboy Bakery. Business model canvas for our new product also has been explained in this report. Business model canvas or BMC has nine building blocks which are customer segment, customer relationship, channel, key partners, key resources, key activities, revenue streams, value propositions and cost structures. In this company need to decide which segments to serve and which segment to ignore. Next, value proposition is summarize why a customer should try our products. Channel can be defined how a company communicates with and reach its customer segments to deliver its value proposition. Furthermore, customer relationship are dictating the nature of the relationships that an organization will develop with its various customer segments. The most important is revenue stream. It is told about how the company will make money. In business model canvas block also contain about key activities, key partner, cost structure and the last one is key resources.